RETI IR VERTINGI LIETUVIŠKI KONTRAFAKCINIAI LEIDINIAI (1865–1904) KAUNO APSKRITIES VIEŠOJOJE BIBLIOTEKOJE - DAMBRAUSKIENĖ, RAMUNĖ (Knygotyra, 2011)
Kauno apskrities viešoji biblioteka Radastų g. 2, LT-44164 Kaunas, Lietuva El. paštas: ramuned@kvb.lt Spaudos draudimo metais leisti lietuviškieji kontrafakciniai leidiniai užima svarbią vietą tarp Kauno apskrities viešojoje bibliotekoje saugomų spaudos paveldo objektų. Straipsnyje nagrinėjama šių leidinių repertuaro sudėtis, egzempliorių savybės, įrišimai, knygos ženklai, marginalijos. Dėl istoriškai susiklosčiusių kontrafakcijų gamybos bei sklaidos aplinkybių, caro valdžios vykdomo persekiojimo dauguma išlikusių leidinių yra reti. Turimi duomenys leidžia daryti išvadą, kad kontrafakcijų rinkinio knygos dėl retų egzempliorių, rankraštinių įrašų kirilika ir lotyniškais rašmenimis, marginalijų ir kitų knygos ženklų yra vertingas knygos ir kultūros istorijos tyrinėjimų šaltinis. Reikšminiai žodžiai: nacionalinė bibliografija, knygos istorija, spaudos draudimas, kontrafakcijos, spaudos paveldas, knygų įrišimai, knygos ženklai, proveniencijos, marginalijos. RARE AND VALUABLE LITHUANIAN CONTRAFACTIONS (1865–1904) OF THE KAUNAS COUNTY PUBLIC LIBRARY RAMUNĖ DAMBRAUSKIENĖ Abstract Old and Rare Books Department of the Kaunas County Public Library (further referred to as KCPL) preserves over 200 thousand copies of books, periodicals, maps, manuscripts from the 15th–mid 20th century in Lithuanian and foreign languages. Written cultural heritage stored in the library is the only heritage of this type in Kaunas County and the largest among all County Public Libraries of Lithuania. An important part of the collection is Lithuanian contrafactions published in the press prohibition period (1864–1904). The collection contains 465 publications of 218 titles, which constitute 26.2 percent of all published contrafactions (833). According to the presently known statistics, 41.7 percent of the contrafactions stored at the KCPL are rare (up to 10 remaining copies); among them, there are 2 unique publications, 12 rarities, 19 especially rare publications. The major part of the collection consists of religious publications: prayer-books, saints’ lives, ascetic literature, etc. One fifth of the collection consists of secular books: fiction, calendars, household-practical books, etc. The low quality of polygraphy and artistry of their bindings are mostly due to contrafaction production and distribution conditions. Books were published at a low price, paperback, small in size and volume. More impressive were only prayer-book bindings. In the collection, 185 books are marked with various ownership insignias. There were found 255 book insignias: 124 institutional and personal stamps, 111 manuscript inscriptions, 12 glue marks, 4 ex-librises, 4 super-ex-librises; 51 books contain marginalia, mostly those from the Samogitian Priest Seminary Library. Manuscript inscriptions written in the Cyrillic alphabet show the influence of the press prohibition period on the culture of Lithuanian script. Provenances of the KCPL contrafactions, marginalia, book binding, etc. reflect the reading culture of the late 19th–early 20th century and are a source for the further investigation of the book and script history. The KCPL contrafactions are a significant supplement of national bibliography: 321 copies are not registered in the publications of retrospective national bibliography and in the data-bank of the Bibliography and Book Science Centre of the National Library. This written heritage is valuable for the Kaunas region for its amount and content, which represents the period of press prohibition. The second stage of creating virtual libraries, which has started in regional libraries, will guarantee the preservation and spread of this heritage. rif’; text-transform: uppercase;">